2015
DOI: 10.5530/pj.2015.5.5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Acetyl Cholinesterase Inhibitory assay of Acacia catechu Willd Ethanolic Seed Extract

Abstract: Aim & objective:The aim of this study was to evaluate acetyl cholinesterase inhibitory activity of Acacia catechu ethanolic seed extract to introduce a new source for management of Alzheimer's disease. Background: Alzheimer's disease is a complex, multifactorial, progressive, neurodegenerative disease primarily affecting the elderly population and is estimated to account for 50-60% of dementia cases in persons over 65 years of age. It is likely that the inhibition of acetyl cholinesterase by Acacia catechu eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE,pseudocholinesterase) enzymes were inhibited by methanolic extracts of grape (Vitisvinifera L.) seeds [30]. In studies with Acacia catechu willd, Cola acuminata, Cuminum cyminum and Lawsonıa Inermıs (Henna) seeds, IC50 values of seed extracts were found as 204.38 = ± 2.54 (ug/mL) [31], 14.6 ± 1.04 (𝜇g/mL) [32], 0.437μg/mL [33] and 66.6 (mg/L) [34] respectively. Similar to the literature, it was observed that selected seed extracts had inhibitory effects on the enzyme activity (Table 1, Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE,pseudocholinesterase) enzymes were inhibited by methanolic extracts of grape (Vitisvinifera L.) seeds [30]. In studies with Acacia catechu willd, Cola acuminata, Cuminum cyminum and Lawsonıa Inermıs (Henna) seeds, IC50 values of seed extracts were found as 204.38 = ± 2.54 (ug/mL) [31], 14.6 ± 1.04 (𝜇g/mL) [32], 0.437μg/mL [33] and 66.6 (mg/L) [34] respectively. Similar to the literature, it was observed that selected seed extracts had inhibitory effects on the enzyme activity (Table 1, Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Though, there is only one clinical trial that examined the effectiveness of this medicinal supplement. Flavocoxid was found to decrease the physical symptoms linked with knee osteoarthritis in a double-blind randomized prohibited examination using 253 volunteers diagnosed with low-to-me osteoarthritis 72 . Naproxen (440 mg/day) was used and the clinical results of the botanical mixture were similar with or even greater to naproxen.…”
Section: Analgesic Anti-inflammatory and Antipyretic Activitiesmentioning
confidence: 99%